The study of anhedonia level among the city of kiev and kiev region residents who were under quarantine due to covid-19 pandemic - Orlova, Nataliia; Tarasov, Volodymyr; Shkliar, Mykhailo (Psychosomatic Medicine and General Practice, 2020)
Background: Coronavirus has rapidly spread worldwide for several months. Ukraine, like many other countries, was affected by a pandemic. As in most countries of the world, due to the rapid spread of coronavirus infection, Ukraine has established a quarantine at the state level, which restricts the movement of citizens and appeal for staying at home. COVID-19 has affected many aspects of life in the country. The unpreparedness of Ukrainian medicine, people’s fatigue from everyday problems and other aspects - all these factors are also affected the mental health of the Ukrainians during a pandemic. We tried to find out how being quarantined through COVID-19 affected the emotional and hedonic background of Ukrainians living in the capital of Ukraine, the city of Kyiv and adjacent Kyiv region. Materials and methods: The study was conducted during 62 days of officially announced quarantine due to COVID-19: from March 12 to May 11, 2020 inclusive. The study voluntarily involved 68 residents of Kyiv and Kyiv region who did not have mental disorders at the time of the interview. We used the Anhedonia Scale (Snight-Hamilton Pleasure Scale, SHPS) and the scale for assessing psychological health and quality of life (General Well-Being scale, GWBS). Interviews with respondents during quarantine were conducted using modern telecommunications technologies (e.g, Skype, Zoom, contacts via social networks, etc.). But there were also regular interviews with answerers if they needed psychological help. Results and conclusions: The study revealed the presence of anhedonia in one third of respondents, which turned out to be about 10 percent more than among respondents without distress. It was found that anhedonia was observed more often in women than in men. These data are different from those obtained in the survey in a normal situation. The anhedonia of social contacts and interactions was most noticeable. The survey also noted expressed anxiety, tension, and fear for the own health of respondents, their loved ones, and relatives as well.